Membangun Jiwa Entrepreneurship Mahasiswa melalui Bisinis Teknologi Digital - Winarti Winarti; Lisna Amelia; Yona Wahyuningsih (Departement of Mathematics Education, 2022)
In line with the development of increasingly global and sophisticated digital technology, this can be a great opportunity to be utilized, especially in the business sector or to create creative ideas. The purpose of this research is to build student entrepreneurship through digital business with creative new ideas and innovations as well as the rapidly growing role of digital technology and how to use it. Because it can be seen from the current conditions that there are opportunities for sophisticated digital technology but cannot be exploited or used for positive things. In this study using qualitative research methods or descriptive approach. In this study, the data sources obtained were the results of literature studies from various reference sources such as journals, articles and books. The data obtained from these sources to support this research. The results of this study have implications that with the development of digital technology, especially students are able to utilize and follow the development of digital technology which is increasing rapidly so that it will create new jobs and reduce the number of unemployed. In addition, it is able to improve the economy in Indonesia which is experiencing a crisis and catching up with other countries.